Processing of X65MoCrWV3‐2 Cold Work Tool Steel by Laser Powder Bed Fusion. Issue 5 (16th December 2019) - Boes, Johannes; Röttger, Arne; Theisen, Werner
Abstract : Laser powder bed fusion (L‐PBF) of forming tools has become of major interest in the tooling industry because of the high geometrical flexibility of this process. During L‐PBF, a metallic powder bed is melted selectively by a laser beam, enabling the layer‐wise manufacturing of parts from 3D computer‐aided design data. The process is characterized by a locally and temporally unsteady heat flow in the solidified part and in the melt pool, causing nonequilibrium solidification and phase transformations. In addition, rapid heating and cooling occur, promoting the formation of microstructural defects, cold cracks, and distortion. Because of the high tendency to form cold cracks, processing of martensitic tool steels is still a challenging task. Tool steel X65MoCrWV3‐2 is processed by L‐PBF and the resulting microstructure and the associated local properties are investigated by microhardness measurements, nanoindentation, and scanning electron microscopy. It is gathered from the investigations that regions of different microstructures and mechanical properties on both micro‐ and macroscale are present in the L‐PBF‐densified steel. The different microstructures and properties are the result of the alternating heat insert at different temperature regimes, forming heat‐affected zones in which the tempering processes are triggered and strongly varying properties are generated. Abstract : X65MoCrWV3‐2 tool steel manufactured by laser powder bed fusion (L‐PBF) is investigated. After solidification, the steel shows a hard martensitic microstructure induced by the high cooling rates during L‐PBF. Repeated heat input caused by the melting of the subsequent layers induces partial reaustenitization and in situ tempering of the martensite, thermally stabilizing the microstructure.